The Urgency of Protecting Netizen in Freedom of Speech on Social Media - Priyanto, Grandis Ayuning; Sardi, Martinus (Faculty of Law Universitas Muhamadiyah Yogyakarta, 2020)
Freedom of speech is a part of fundamental rights to every people. Nowadays, freedom of speech could not felt widely to all people. Freedom of speech developed until Universal Declaration of Human Rights and International Covenant on Civil and Political Rights assure and restrict freedom of speech. In Indonesia, since the rise of The Law of Information and Electronic Transaction, the restriction of freedom of speech become biased, many words in social media are presumably attack others. Netizen feels security to speak up is limited, such Ruslan Buton who critics and record about President Jokowi deemed as a hoax and hate speech. Even though some articles in 1945 Constitution have already protect and guarantee all people to bear the right to speak. The limitations of Freedom of speech in The Law of Information and Electronic Transaction emerge multi interpretation which the right to speak have not been correspond with the values in 1945 Constitution. To harmonize freedom of speech in Indonesia, it needs cooperation among government and people to eradicate ambiguity and fear in which already happen.By using juridical-normative method, the research aims to understand the condition of freedom of speech in Indonesia, and to understand the protection of netizen in using social media